When the lights go down - Brickell, Edie; Simon, Paul; Halee, Roy; Geffen Records (United States : Geffen Records, 1994)
Contains the long playing version of the song.
CD 1 : When The Lights Go Down (LP version) / (3:48).
Title from disc label.
Keywords: Songs, English